Testing Sex, Attributing Gender - Susan Cahn (University of Kansas Libraries, 2011)
The highly-publicized case of Caster Semenya is a symptom of deeper problems that continue to plague women athletes at all levels-biased gender identification and a belief that sport and femininity do not mesh. I trace my own path through the thickets of "angry feminism," a love of sports, stereotypes of the "fair" sex, and a 4-year-old nephew's confused claim that Aunt Susan is a man. I examine symbols, body parts, gestures, clothing and other means by which men and women are unevenly (and often inaccurately and unfairly) identified. I note that in spite of new opportunities enjoyed by women to run, jump, compete and otherwise celebrate their physicality, female athletes still struggle to maintain their identity as "normal." I see dangers in a world that forces its citizens into one of two gender boxes, but I also acknowledge gender as an important part of human identity and sporting opportunity. I conclude that I do not have any solutions, only questions. But I am certain that we should be able to play in a world where none of us is robbed of our joy.